Review of Psychological Interventions in Oncology: Current Trends and Future Directions - Teodora Anghel; Bratu Lavinia Melania; Iuliana Costea; Oana Albai; Amalia Marinca; Codrina Mihaela Levai; Lavinia Maria Hogea (Medicina)
Background and Objectives: Cancer imposes a profound burden on both physical and psychological health, particularly at advanced stages, which are associated with a poor prognosis and heightened emotional distress. Psychotherapeutic interventions have gained recognition for their role in alleviating distress, enhancing the quality of life, and supporting a holistic approach to cancer care. This review examines the effectiveness of psychotherapeutic interventions in improving psychological well-being in cancer patients. Materials and Methods: Conducted as a literature review following PRISMA guidelines, this study analyzed experimental research on psychotherapeutic interventions for cancer patients published in the past decade. Literature searches were performed in PubMed, Google Scholar, the Cochrane Library, Web of Science, PsycINFO, and Consensus, supplemented by manual reference checks. The inclusion criteria focused on randomized controlled trials (RCTs). Results: The analysis included 20 RCTs spanning over three decades, evaluating interventions such as individual meaning-centered psychotherapy (IMCP), Mindfulness-Based Cognitive Therapy (MBCT), and supportive–expressive group therapy (SEGT). IMCP emerged as being particularly effective in reducing depression, anxiety, and demoralization while enhancing spiritual well-being. MBCT demonstrated significant reductions in the fear of recurrence, while SEGT effectively addressed traumatic stress and fostered social support. Although the survival benefits were inconsistently reported, psychosocial improvements, including an enhanced quality of life and emotional resilience, were consistently observed. The methodological quality varied, with nine studies meeting high-quality standards. Conclusions: Psychotherapeutic interventions, particularly IMCP and MBCT, play a critical role in oncology by alleviating distress, fostering resilience, and improving the quality of life. Integrating these approaches into routine cancer care can ensure a more holistic treatment framework that prioritizes the emotional and psychological needs of patients.